PROVIDING AFFORDABLE HOUSING FOR LOW-INCOME GROUPS - Handayani, Teti (Jurnal Natah, 2004)
The rapid urban population growth led to an increase in demand of housing as one of the basic needs. Housing demand refers to the total need for houses regardless of economic possibilities to afford housing.The number of housing constructed by formal sector could not contribute substantially to alleviate the housing shortage, especially housing for low-income groups. Moreover, the price of formal housing is too expensive for the target groups.This paper try to describe some cost reduction approaches in order to provide better access for low-income groups to housing in the formal sector.